Double orifice mitral valve associated with ostium primum atrial septal defect: (case report) - Saylam, Argun; Oram, Aysel; Nazlı, Nasih; Yener, Ali; Aytac, Aydın (The Turkish Journal of Pediatrics, 1976)
A case of primum type atrial septal defect and double orifice mitral valve, where no surgical intervention was done for the duplicated mitral valve, because of the hemodynamically insignificant mitral regurgitation is presented. Literature concerning this rare pathology is reviewed and it was concluded that mitral valve replacement should be the treatment of choice if mitral regurgitation is important hemodynamically and closure of the smaller orifice is not compatible with normal mitral valve function. Cutting the central bar between the two mitral orifices should be tried first in cases of mitral stenosis. It might be difficult to decide which of the two orifices is incompetent and closure of one of them during the operation may result in postoperative mitral stenosis or insufficiency. Careful examination of the mitral valve is mandatory particularly in cases of partial or complete atrioventricular canals, taking into consideration that this rare malformation of the mitral valve is usually associated with endocardial cushion defects.